A preparation method of degradable suture based on polyelectrolyte method and its application
The polyelectrolyte method generates a degradable suture with a double crosslinked structure, which solves the problems of complex preparation and drug residues in the prior art, and achieves high-strength and good biocompatible sutures, which are suitable for a variety of applications.
Patent Information
- Application Number
- CN202211054354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The preparation method of degradable sutures in the prior art is complex, which may lead to drug residues and performance impacts, and the mechanical strength is not sufficient to meet medical requirements.
Using a polyelectrolyte method, chitosan solution and sodium alginate solution are added dropwise to form an interface, fibers are generated through continuous interface reaction, and a double crosslinking structure is obtained through calcium ion crosslinking to prepare high-strength degradable sutures Line, process is gentle and drug residues are left.
It realizes simple and easy preparation of high-strength degradable sutures, has good biocompatibility, antibacterial and anti-inflammatory properties, and is suitable for different application scenarios.
Smart Images

Figure CN115400257B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sutures, and in particular to a preparation method of a degradable suture based on a polyelectrolyte method and an application thereof. Background Art
[0002] Chitosan fiber is a natural material with the advantages of being non-toxic, hemostatic, and anti-inflammatory. It has good compatibility with biological cells, low immunogenicity, and will not produce rejection reactions with body fluids and cells. It is biodegradable and is often used in the medical field. However, due to its material, the mechanical strength of chitosan fiber is not high. The breaking strength of chitosan fiber obtained by conventional spinning is only 1.07 cN / dtex, which cannot meet the application requirements of medical sutures.
[0003] In order to solve the strength problem of chitosan fiber, there is a high-strength medical suture for children and a preparation method thereof, the publication number of which is CN114808229A. In this invention patent, the preparation method of the suture disclosed is to immerse the chitosan fiber in a solution containing polyvinyl alcohol and glutaraldehyde for cross-linking, and perform high temperature operation, freezing cycle and other treatments.
[0004] The technical problems of this method are as follows: it uses polyvinyl alcohol, glutaraldehyde and other methods to cross-link chitosan, and the introduced chemical substances cannot be completely removed, which may cause toxic effects in the later stage; and this method uses irradiation sterilization method, which causes the loaded drug protein to denature and lead to loss of efficacy; and the preparation method of the degradable suture is relatively complicated, and the design of high temperature operation at 70-80°C, freezing cycle and other methods may affect its drug structure and affect the final performance of the product. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method of a degradable suture based on a polyelectrolyte method and its application, so as to solve the technical problems of the prior art that the preparation method of the degradable suture is complicated and has drug residues.
[0006] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0007] The present invention provides a method for preparing a degradable suture based on a polyelectrolyte method, comprising the following steps:
[0008] S100, dropping the chitosan solution and the sodium alginate solution onto the hydrophobic surface, and the two liquids adhere to form an interface;
[0009] S200, pulling out the polyelectrolyte on the interface to form a continuous interface reaction to obtain fibers;
[0010] S300, sequentially subjecting the fiber to a cross-linking agent, sterile water, and an ethanol solution to prepare a degradable suture.
[0011] As a preferred embodiment of the present invention, in S200, the fibers are continuously formed in the continuous interface reaction.
[0012] As a preferred solution of the present invention, it is characterized in that, in S200, the pulling force on the fiber is negatively correlated with the diameter of the degradable suture.
[0013] As a preferred solution of the present invention, in S300, the fibers undergo a cross-linking reaction with the cross-linking agent when passing through the cross-linking agent, so that the fibers are arranged in one direction.
[0014] As a preferred embodiment of the present invention, the concentration of ions in the cross-linking agent is in the range of 2-10 mg / mL.
[0015] As a preferred embodiment of the present invention, the molecular weight of chitosan in the chitosan solution is 50W-100W.
[0016] As a preferred embodiment of the present invention, the concentration of the chitosan solution is 1 mg / mL to 10 mg / mL;
[0017] Wherein, the concentration of the sodium alginate solution is 1 mg / mL to 10 mg / mL.
[0018] As a preferred solution of the present invention, in S100, the following steps are also included:
[0019] S101, dissolving the drug into chitosan solution or sodium alginate solution.
[0020] The present invention also provides an application based on the polyelectrolyte method, and a degradable antibacterial and anti-inflammatory suture thread is prepared based on the polyelectrolyte method.
[0021] Furthermore, a single or multiple degradable antibacterial and anti-inflammatory suture is collected in parallel or multiple strands are twisted to form a suture, and then the suture is immersed in a nano antibacterial agent for modification to obtain the antibacterial and anti-inflammatory suture.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention adopts a polyelectrolyte method, that is, an anion-cation polyelectrolyte method, to obtain degradable fibers, and then obtains double-crosslinked structure fibers through ionic crosslinking to prepare degradable sutures. The preparation method is simple and mild, and there is no drug residue.
[0024] 2. The present invention adds drugs or various inorganic or polymer materials during the preparation of the electrolyte solution, thereby being able to give the suture various properties such as antibacterial properties, the ability to promote tissue repair, angiogenesis, etc., so that the suture can match various application scenarios and achieve dedicated use. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0026] Figure 1 The present invention provides a schematic diagram of the process of preparing chitosan-sodium alginate degradable suture based on the polyelectrolyte method;
[0027] Figure 2 The present invention provides different CaCl 2 Scanning electron microscopy observation of the degradable suture after concentration cross-linking;
[0028] Figure 3 The present invention provides CaCl 2 Stress-strain curves for each concentration;
[0029] Figure 4 The present invention provides CaCl 2 Force-displacement curves for each concentration;
[0030] Figure 5 The present invention provides 10 mg / mL chitosan and 10 mg / mL sodium alginate in 10 mg / mL CaCl 2 Force-displacement curves of the sutures made in;
[0031] Figure 6 The present invention provides 10 mg / mL chitosan and 10 mg / mL sodium alginate in 10 mg / mL CaCl 2 Stress-strain curves of sutures made in;
[0032] Figure 7 Provide a cell compatibility evaluation chart for the present invention;
[0033] Figure 8 The present invention provides a SD rat back suture experiment (the left picture is before suture, and the right picture is after suture). DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] like Figure 1 As shown, the present invention provides a method for preparing a degradable suture based on a polyelectrolyte method, comprising the following steps:
[0036] S100, dropping the chitosan solution and the sodium alginate solution onto the hydrophobic surface, and the two liquids adhere to form an interface;
[0037] S200, pulling out the polyelectrolyte on the interface to form a continuous interface reaction to obtain fibers;
[0038] S300, sequentially subjecting the fiber to a cross-linking agent, sterile water, and an ethanol solution to prepare a degradable suture.
[0039] Preferably, the cross-linking agent is one of sterile calcium chloride solution and sterile sodium hydroxide solution.
[0040] Specifically, in this embodiment, sterile chitosan solution (1 mg / mL to 10 mg / mL) and sterile sodium alginate solution (1 mg / mL to 10 mg / mL) of different concentrations are prepared, and two drops of liquid are dropped on a hydrophobic surface (or a chip method is used) to form an interface between the two liquids, and the polyelectrolyte product is pulled out at the interface to form a continuous interfacial reaction and then form fibers; the fibers are respectively passed through a sterile calcium chloride solution (secondary cross-linking), sterile water and sterile alcohol, and then wound into multiple strands to finally obtain a degradable suture.
[0041] The present invention adopts a polyelectrolyte method, namely an anion-cation polyelectrolyte method, to obtain degradable fibers, and then obtains double cross-linked structure fibers through calcium ion cross-linking and other methods for preparation. The preparation method is gentle, has no drug residue, does not require heating, circulation and other treatments, and is simple.
[0042] In this embodiment, in S200, the fibers are continuously formed in the continuous interface reaction.
[0043] The sterile chitosan solution is a cation and the sterile sodium alginate solution is an anion. During the contact process, the interface of the two reacts to form a viscous polyelectrolyte. The polyelectrolyte forms fibers due to mutual adhesion during the pulling process. As the sterile chitosan solution and the sterile sodium alginate solution continue to react, the fibers gradually increase during the pulling process. The pulled fibers are then cross-linked with a cross-linking agent, sterile water, and ethanol solution in turn to make a continuous and unbreakable degradable suture.
[0044] Furthermore, in S200, since the pulling force on the fiber is negatively correlated with the diameter of the degradable suture, in the process of pulling out the fiber, it is necessary to regulate the pulling force, such as keeping the pulling force unchanged so that the diameter of the degradable suture remains unchanged, which is convenient for subsequent processing and suturing.
[0045] Further, in this embodiment, when calcium chloride solution is used as a cross-linking agent, Figure 2 As shown, in S300, the fibers undergo a cross-linking reaction with the cross-linking agent when passing through the cross-linking agent, so that the fibers are arranged in one direction.
[0046] In order to accurately obtain the diameter of the degradable suture, a scanning electron microscope was used to characterize it. The results show that after the cross-linking agent calcium chloride, its diameter increased significantly. And through observation, it can be seen that the diameter of the suture is relatively uniform, and the fibers are arranged in a unidirectional manner.
[0047] In this example, in order to explore the optimal concentration of the cross-linking agent and the optimal molecular weight of chitosan, a universal mechanical tester was used to perform mechanical characterization on degradable sutures of different components and diameters on the basis of controlling variables.
[0048] In this embodiment, calcium chloride solution was used as a cross-linking agent, and the mechanical properties of the degradable sutures with different calcium chloride concentrations and different molecular weight chitosan were characterized by a universal mechanical tester. The results show that ( Figure 3 ): After cross-linking with 10 mg / mL of calcium chloride, its tensile modulus is the highest, reaching 250 MPa, exceeding the FDA standard of 220 MPa; and 2 mg / mL is 214 MPa, close to its standard, so we chose 2-10 mg / mL of calcium chloride as the cross-linking enhancer this time; and the degradable sutures cross-linked with pure polyelectrolyte without calcium chloride cross-linking cannot meet the standard requirements.
[0049] Table 1. Calcium chloride concentration and suture diameter
[0050] Calcium chloride concentration 0% 2% 3% 5% 8% 10% Diameter(μm) 115±3 180±5 142±5 170±5 200±3 170±5
[0051] The force-displacement curves of 16 degradable sutures were also made. Figure 4As shown, 10 mg / mL calcium chloride has the highest elongation.
[0052] 10 mg / mL chitosan, 10 mg / mL sodium alginate, 10 mg / mL CaCl 2 For example, taking the molecular weight of chitosan as a variable, Figure 5 and Figure 6 It can be seen that among the effects of chitosan molecular weight, chitosan with a molecular weight of 50W has the highest tensile strength modulus, while chitosan with a molecular weight of 100W has the largest breaking tensile force, but its diameter is thicker and its tensile strength is smaller. Therefore, the molecular weight of chitosan in the chitosan solution is 50W-100W, which is the best.
[0053] Preferably, the concentration of the chitosan solution is 1 mg / mL to 10 mg / mL.
[0054] Preferably, the concentration of the sodium alginate solution is 1 mg / mL to 10 mg / mL.
[0055] In order to verify that the degradable suture described in this example has no obvious cytotoxicity, the degradable suture was co-cultured with different cells (human umbilical vein endothelial cells, rat mesenchymal stem cells, chondrocytes), and 1 cm of the suture was added to a 24-well plate using the Transwell method and cultured for 6 h and 24 h to obtain cytotoxicity. Figure 7 It can be seen that the degradable suture prepared by this method has no obvious cytotoxicity
[0056] In order to verify that the degradable suture described in this example can be used as wound suture, the prepared suture was used to suture the back wound of SD rats. Figure 8 It can be seen that the experiment proves that the prepared degradable suture can be used as wound suture.
[0057] Furthermore, since the above preparation method is simple and easy to implement, and the conditions are mild, the raw materials can also be loaded with drugs during the preparation process. In S100, the following steps are also included:
[0058] S101, dissolving the drug into chitosan solution or sodium alginate solution.
[0059] The drug is dissolved in a chitosan solution or a sodium alginate solution, and then a suture is prepared according to the above preparation method, and finally a drug-loaded suture can be obtained.
[0060] The present invention also includes an antibacterial and anti-inflammatory suture, which is made from the degradable suture made by any one of the above-mentioned preparation methods.
[0061] The method for preparing the antibacterial and anti-inflammatory suture comprises the following steps:
[0062] The degradable sutures prepared by any of the above preparation methods are collected in parallel or twisted into a suture; then the sutures are immersed in a nano antibacterial agent and modified to obtain the antibacterial and anti-inflammatory sutures.
[0063] Nano antimicrobial agents include but are not limited to nano bioactive glass, bioactive glass fiber, nano gold, nano silver and the like.
[0064] Through the preparation and application of the chitosan-sodium alginate degradable suture based on the polyelectrolyte method of this embodiment, the tensile strength of the suture can be greater than 250Mpa, and it has good biocompatibility; and this preparation method is simple and easy, the conditions are mild, and it can be relatively simple to load drugs and inorganic materials (nanomaterials, mesoporous materials, etc.), and in application, the suture is given antibacterial and anti-inflammatory properties, and tissue repair properties such as osteovascularization are promoted, thereby forming a degradable suture suitable for different parts.
[0065] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present application. The protection scope of the present application is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present application within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present application.
Claims
1. A method for preparing a degradable suture based on a polyelectrolyte method, characterized in that: The steps include: S100, dropping the chitosan solution and the sodium alginate solution onto the hydrophobic surface, and the two liquids adhere to form an interface; S200, pulling out the polyelectrolyte on the interface to form a continuous interfacial reaction to obtain fibers, wherein the fibers are continuously formed in the continuous interfacial reaction; S300, sequentially subjecting the fiber to a cross-linking agent, sterile water, and an ethanol solution to prepare a degradable suture; In S300, the fibers undergo a cross-linking reaction with the cross-linking agent when passing through the cross-linking agent, so that the fibers are arranged in one direction; The cross-linking agent is a sterile calcium chloride solution; The concentration range of ions in the cross-linking agent is 2-10 mg / mL; The molecular weight of chitosan in the chitosan solution is 50W-100W; The concentration of the chitosan solution is 1 mg / mL to 10 mg / mL; Wherein, the concentration of the sodium alginate solution is 1 mg / mL to 10 mg / mL; In S200, the pulling force on the fiber is negatively correlated with the diameter of the degradable suture.
2. A degradable antibacterial and anti-inflammatory suture, characterized in that: The degradable suture obtained by the preparation method of claim 1 is prepared by collecting a single or multiple degradable sutures in parallel or twisting multiple strands to form a suture, and then immersing the suture in a nano-antibacterial agent for modification to obtain a degradable antibacterial and anti-inflammatory suture.
Citation Information
Patent Citations
High-strength medical suture for children and preparation method thereof
CN114808229A
Sodium alga acid / chitosan composite fluid spinning method
CN101665995A